Universities, collections, university museums and sociomuseology: a hybrid network of dialogues (Cadernos de Sociomuseologia, 2023)
This article intends to analyze the contemporary context of Brazilian collections and university museums from the perspective of sociomuseology. Data from this specific category of museums are presented, here called in their heterogeneous set as University Museological Nucleus. Aspects of its potential and challenges for social demands are presented, with emphasis on the inclusion of contemporary museum processes that seek to insert inclusive narratives within traditional structures, in academic environments, historically constituted. The objective is to develop a reflection based on texts that address aspects of the museum field in built spaces, or even in projects, that operate in higher education institutions, in the field of research, teaching and cultural extension, based on collections formed for academic purposes, and that currently intend to expand their original attributions, to glimpse the society, from the perspective of their individuals as historical agents. The cooperation networks are inserted in the present study as a systemic complex, constituting themselves as an action strategy in the face of social challenges for the communication of university museological heritage. Here we are not looking for conclusions and directions, but the construction of a discourse that can contribute to the instigating debate on the relationship between sociomuseology, museums and universities.Key words: University museums; University; Sociomuseology; Cooperation networks.